Pengetahuan Wanita Usia Subur Tentang Kontrasepsi Pil - Farunti Iga Melani; Liberty Barokah (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background; in choosing the type of contraception, one of which is the level of knowledge of the family planning acceptors candidate. Mother's high knowledge will influence the choice of contraception. The higher a person's level of knowledge, the more observant the person is in determining the contraceptive method. Method; Research design using quantitative descriptive with cross sectional approach. Respondents of the study were 86 women with a purposive sampling technique that had met the exclusion and inclusion criteria. The analysis was carried out using the percentage form based on the frequency of each category. Result; shows that knowledge of WUS about pill contraception is sufficient for 43 people (50%), knowledge of understanding is sufficient for 33 people (38.37%), less profit is 39 people (45.35%), less loss is 50 people (58.14%) 43 people (50%) started using enough and 35 people (40.69%) were drinking enough. Conclusion; sufficient knowledge about the meaning, when to start drinking and how to take contraceptive pills and insufficient knowledge about the advantages and disadvantages of contraceptive pills